Tiragolumab plus atezolizumab versus placebo plus atezolizumab as a first-line treatment for PD-L1-selected non-small-cell lung cancer (CITYSCAPE): primary and follow-up analyses of a randomised, double-blind, phase 2 study. Issue 6 (June 2022) - Cho, Byoung Chul; Abreu, Delvys Rodriguez; Hussein, Maen; Cobo, Manuel; Patel, Anjan J; Secen, Nevena; Lee, Ki Hyeong; Massuti, Bartomeu; Hiret, Sandrine; Yang, James Chih Hsin; Barlesi, Fabrice; Lee, Dae Ho; et al.
Summary: Background: Targeted inhibition of the PD-L1–PD-1 pathway might be further amplified through combination of PD-1 or PD-L1 inhibitors with novel anti-TIGIT inhibitory immune checkpoint agents, such as tiragolumab. In the CITYSCAPE trial, we aimed to assess the preliminary efficacy and safety of tiragolumab plus atezolizumab (anti-PD-L1) therapy as first-line treatment for non-small-cell lung cancer (NSCLC). Methods: CITYSCAPE is a phase 2, randomised, double-blind, placebo-controlled trial. Patients with chemotherapy-naive, PD-L1-positive (defined as a tumour proportion score of ≥1% by 22C3 immunohistochemistry pharmDx assay; Dako, Agilent Technologies, Santa Clara, CA, USA) recurrent or metastatic NSCLC with measurable disease, Eastern Cooperative Oncology Group performance status of 0 or 1, and no EGFR or ALK alterations were enrolled from 41 clinics in Europe, Asia, and the USA. Patients were randomly assigned (1:1), via an interactive voice or web-based response system, to receive tiragolumab (600 mg) plus atezolizumab (1200 mg) or placebo plus atezolizumab intravenously once every 3 weeks. Investigators and patients were masked to treatment assignment. The co-primary endpoints were investigator-assessed objective response rate and progression-free survival as per Response Evaluation Criteria in Solid Tumors version 1.1 in the intention-to-treat population, analysed after approximately 80 progression-free survival events had been observed in the primary population. Safety was assessed in all patients who received at least one dose of study drug. This trial is registered with ClinicalTrials.gov, NCT03563716, and is ongoing. Findings: Patients were enrolled between Aug 10, 2018, and March 20, 2019. At data cutoff for the primary analysis (June 30, 2019), 135 of 275 patients assessed for eligibility were randomly assigned to receive tiragolumab plus atezolizumab (67 [50%]) or placebo plus atezolizumab (68 [50%]). In this primary analysis, after a median follow-up of 5·9 months (4·6–7·6, in the intention-to-treat population, 21 patients (31·3% [95% CI 19·5–43·2]) in the tiragolumab plus atezolizumab group versus 11 patients (16·2% [6·7–25·7]) in the placebo plus atezolizumab group had an objective response (p=0·031). Median progression-free survival was 5·4 months (95% CI 4·2–not estimable) in the tiragolumab plus atezolizumab group versus 3·6 months (2·7–4·4) in the placebo plus atezolizumab group (stratified hazard ratio 0·57 [95% CI 0·37–0·90], p=0·015). 14 (21%) patients receiving tiragolumab plus atezolizumab and 12 (18%) patients receiving placebo plus atezolizumab had serious treatment-related adverse events. The most frequently reported grade 3 or worse treatment-related adverse event was lipase increase (in six [9%] patients in the tiragolumab plus atezolizumab group vs two [3%] in the placebo plus atezolizumab group). Two treatment-related deaths (of pyrexia and infection) occurred in the tiragolumab plus atezolizumab group. Interpretation: Tiragolumab plus atezolizumab showed a clinically meaningful improvement in objective response rate and progression-free survival compared with placebo plus atezolizumab in patients with chemotherapy-naive, PD-L1-positive, recurrent or metastatic NSCLC. Tiragolumab plus atezolizumab was well tolerated, with a safety profile generally similar to that of atezolizumab alone. These findings demonstrate that tiragolumab plus atezolizumab is a promising immunotherapy combination for the treatment of previously untreated, locally advanced unresectable or metastatic NSCLC. Funding: F Hoffmann-La Roche and Genentech.